The effect of agricultural waste biochar on the availability of silicon in ultisol and inceptisol under flooded conditions. Issue 1 (1st December 2022) - Widijanto, H; Suntoro; Mujiyo; Syamsiyah, J
Abstract: The research was conducted to know the effect of several kinds of biochar on the availability of Silicon (Si) on different soils in a flooded condition. The experiment used a complete randomized design (CRD) with two factors: biochar and soil type. Biochar type consists of B1 = rice straw; B2 = rice husk; B3 = sawdust; B4 = coconut shell; B5 = corn stover. Soil type consists of T1= Inceptisol and T2 = Ultisol. Each treatment is replicated three times. The experiment used 2 kg of soil, and the dose of biochar was 5 tons.ha −1 . Incubation is carried out for four weeks by maintaining a water height of 5 cm. Soil observation parameters include organic carbon, total Si, available Si, water leached Si, and pH H2 O. The data were analyzed using Analysis of Variance with 95% and 99% confidence levels, Duncan's Multiple Range Test, and Correlation Test. The results showed that rice husks biochar has a higher total Si and available Si than other biochar. Rice husk biochar gives the highest available Si of Inceptisol (8.66 mg.kg −1 ) and Ultisol (7.49 mg.kg −1 ) compared to the other biochar. Silicon leaching ranges from 5.23-8.66% of soil available Si in both soils.